Global health education in UK medical schools: a review of undergraduate university curricula - Bethan Davies; Helen Ward; Natasha Roya Matthews (BMJ Global Health)
Introduction In recognition of our increasingly globalised world, global health is now a required component of the medical school curriculum in the UK. We review the current provision of global health education (GHE) in UK medical schools to identify gaps in compulsory teaching.Methods We conducted a review of the literature to inform a two-part electronic survey of global health compulsory teaching, optional teaching and pre-elective training. Surveys were sent to all 33 UK medical schools for completion by the faculty lead on global health and the nominated final year student representative.Results Surveys were returned by 29 (88%) medical school faculty and 15 (45%) medical student representatives; 24 (83%) faculty and 10 (67%) students reported including GHE in the core curriculum; however, there was wide variation in the learning outcomes covered. On average 75% of faculty and 82% of students reported covering recommended global health themes ‘global burden of disease’, ‘socioeconomic and environmental determinants of health’, ‘human rights and ethics’, and ‘cultural diversity and health’, while only 48% of faculty and 33% of students reported teaching on ‘health systems’ and ‘global health governance’. Almost all institutions offered optional global health programmes and most offered some form of pre-elective training, although content and delivery were variable.Conclusion Over the last decade, the inclusion of global health in the core curriculum of UK medical schools has increased dramatically. Yet, despite interest among students, significant gaps are apparent in current GHE. Governing bodies in medical education should establish a comprehensive national strategy to help improve access to fundamental GHE for all medical students.